Kualitas Pelayanan Pembuatan Akta Kelahiran Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Simalungun - manik, Agustina; Adam, Adam; Batubara, Beby Masitho (Jurnal Pemerintahan dan Politik, 2024)
The purpose oh this study was to determine the quality of service for making birth certificates at the population and Civil Registry Office of Simalungun Regency as well as barriers to service quality in making birth certificates at the Population and Civil Registry Office of Simalungun Regency. The problems found are the level of public awareness is still low, the lack of socialization provided by the Office to the community, the distance from the sub-district location, and the network system is not good. The research method that the researcher uses is descriptive qualitative research method. Data were collected based on data collection techniques by conduting interviews, observations, documentation, and literature studies. The data analysis technique that the researcher uses is data collection, data reduction, data presentation, and drawing conclusions. The theory that researchers use is the theory of service quality according to Zeithaml, namely tangibles, reliability, responsiveness, assurance, empathy. The result showed that the quality of service at the Department of Population and Civil Registry of Simalungun Regency was quite good even if is notoptimal. This can be seen from the Tangible indicators that have been sufficiently proven with the availability of facilities such as computers and laptops. Responsiveness the given by employees to the community who do not understand the birth certificate requirements. Assurance provided employees are good seen from the timeliness and service according to the SOP and the Empathy that the Department has is very good and also high.